2015
DOI: 10.1103/physrevlett.115.046401
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-Driven Charge and Spin Fluctuations inLaCoO3

Abstract: The spin transition in LaCoO_{3} has been investigated using density-functional theory in combination with dynamical mean-field theory employing continuous time quantum Monte Carlo and exact diagonalization impurity solvers. Calculations on the experimental rhombohedral atomic structure with two Co sites per unit cell show that an independent treatment of the Co atoms results in a ground state with strong charge fluctuations induced by electronic correlations. Each atom shows a contribution from either a d^{5}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…2(a) and 2(b), a drastic change is found in the 3d band region around −3 to 0 eV, in contrast to a minor change of the O 2p band around −8 to −3 eV. The PDOS and its change across the spin transition are consistent with previous LDA+DMFT studies, [15][16][17] which provides a validity to our treatment of the band structure of LaCoO 3 . In Fig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…2(a) and 2(b), a drastic change is found in the 3d band region around −3 to 0 eV, in contrast to a minor change of the O 2p band around −8 to −3 eV. The PDOS and its change across the spin transition are consistent with previous LDA+DMFT studies, [15][16][17] which provides a validity to our treatment of the band structure of LaCoO 3 . In Fig.…”
supporting
confidence: 89%
“…13) The DMFT is known as an efficient method to describe the electronic structure of strongly correlated electron systems, 14) and as for LaCoO 3 , the band-structural change due to the HS-LS transition is described quantitatively by a band calculation combined with the DMFT. [15][16][17] One of the advantages of our framework in the analysis of the Co 2p XPS of LaCoO 3 is that many-particle effects including the Co spin state are renormalized within the DMFT scheme, and the correlated 3d band structure is appropriately mapped onto the hybridization structure between the Co impurity and the host in the IAM. Thus, a plausible description of the NLS becomes available, and the spin-state dependence illustrated in Fig.…”
mentioning
confidence: 99%
“…However, this picture is energetically unfavourable at high temperatures when the two HS ions are nearest neighbours. In addition, the breathing type of lattice distortion was not detected by measurements of extended X-ray absorption fine structure (EXAFS) [50], at least up to 330 K. On the contrary, a recent study [51] using dynamical mean-field theory (DMFT) discussed the role of a temperature-dependent Hund's exchange energy and showed that the spin-state transition can be driven purely by electronic means through charge and spin fluctuations. In this scheme, a large Coulomb repulsion will suppress charge fluctuations.…”
mentioning
confidence: 99%
“…Thus, we consistently use U Co = 3 eV throughout this work, in line with previous studies. 8,10,14,18,19 Lower values render too small band gaps at variance with experiments. 34,35 We confirmed our main results by using the rotationally invariant Liechtenstein approach 36 with U = 4 eV and J = 1 eV.…”
Section: Computational Detailsmentioning
confidence: 97%